2019
DOI: 10.1097/md.0000000000018201
|View full text |Cite
|
Sign up to set email alerts
|

Improving the position of resuscitation team leader with simulation (IMPORTS); a pilot cross-sectional randomized intervention study

Abstract: Background: Leadership and teamwork are important contributory factors in determining cardiac resuscitation performance and clinical outcome. We aimed to determine whether fixed positioning of the resuscitation team leader (RTL) relative to the patient influences leadership qualities during cardiac resuscitation using simulation. Methods: A cross-sectional randomized intervention study over 12 months’ duration was conducted in university hospital simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…However, regardless of the leaders’ positioning, active leadership of team leaders, in terms of the total number of leadership statements, was associated with better CPR performance in regards of hands-on times. These results converge with those of Saiboon and colleagues [31] who also reported that the physical positioning of the leader had no effect on situational attentiveness, error detection and decision making. It may be due to the plausibility for the hands-off leader that team leader positioning during resuscitation has hardly been investigated.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, regardless of the leaders’ positioning, active leadership of team leaders, in terms of the total number of leadership statements, was associated with better CPR performance in regards of hands-on times. These results converge with those of Saiboon and colleagues [31] who also reported that the physical positioning of the leader had no effect on situational attentiveness, error detection and decision making. It may be due to the plausibility for the hands-off leader that team leader positioning during resuscitation has hardly been investigated.…”
Section: Discussionsupporting
confidence: 91%
“…[25,27] Behavioral markers in secondary outcomes were leaders' task violation, defined as the time spent with any task deferring from their allocated role in the hands-off or head position respectively (e.g., operating defibrillator in hands-off position); utterances leading to deviation from resuscitation guideline algorithms; Decision Making; Error Detection; and Situational Awareness, following Saiboon and colleagues. [31,32] We adapted and analyzed these parameters as follows:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey instrument was designed based on guidelines, reports, course materials on resuscitation and respiratory disease including COVID-19. 8,[18][19][20] The questionnaire was divided into two parts. Part A was related to the demography of the respondents, comprising age, gender, EHCW designation categories and length of service (LOS) which was defined as the number of years of working as a healthcare provider.…”
Section: Methodsmentioning
confidence: 99%